Efficient Bi-Functional Electrocatalysts of Strontium Iron Oxy-Halides for Oxygen Evolution and Reduction Reactions in Alkaline Media. Issue 6 (1st January 2016) - Ghanem, Mohamed A.; Arunachalam, Prabhakarn; Almayouf, Abdullah; Weller, Mark T.
Abstract : Strontium iron oxyhalide perovskitic oxides were investigated by electrochemical characterization as bi-functional electrocatalysts for oxygen evolution (OE) and oxygen reduction (OR) reactions in alkaline media. The electrochemical investigations showed that the presence of lower levels of oxygen and higher levels of chloride, as in Sr4 Fe3O8 Cl2 and Sr2 FeO2 Cl2 significantly enhanced the oxygen evolution and reduction over the other perovskitic oxides. Additionally, Sr4 Fe3O8 Cl2 and Sr2 FeO2 Cl2 was proven to have high bi-functional activity due to an overpotential gap (ΔE = 0.70 V) between the OER and ORR much lower than that of other similar perovskite bi-functional catalysts. In comparison with other strontium iron oxyhalide based electrocatalysts, Sr2 FeO2 Cl2 was shown to have higher OER activities among all investigated catalysts. This work demonstrates that the oxygen-deficient layered perovskites of the type A2 BO2 X2 are a new class of high-performance electrocatalysts for oxygen evolution (OE) and oxygen reduction (OR) reactions in alkaline media.